2018
DOI: 10.3389/fphys.2018.00378
|View full text |Cite
|
Sign up to set email alerts
|

Spexin Acts as Novel Regulator for Bile Acid Synthesis

Abstract: Spexin is a novel hormone involved in obesity and diabetes while its biofunctional significance in lipid metabolism is still to be comprehended. Global metabolomic analysis in the present study revealed multiple metabolic pathways altered by spexin intraperitoneal (i.p.) injection in rat serum, which are highlighted by the changes in several bile acid metabolites. In rats, spexin (300 μg/kg) could dramatically reduce hepatic and circulating total bile acids (TBA) level compared with the controls. Corresponding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 44 publications
0
31
0
Order By: Relevance
“…Spexin was coevolved with the galanin/kisspeptin family, and it was confirmed that spexin could activate GALR2/3 receptors [ 4 ]. GALR2 antagonist M871 and GALR3 antagonist SNAP37889 had been used to the role of spexin in gastrointestinal motility [ 11 ], inflammatory pain [ 16 ], bile acid synthesis [ 8 ], lipolysis [ 24 ], and in vivo or in vitro studies. Our result demonstrated that SNAP37889 ( p < 0.05), not M871 ( p =0.430), significantly antagonized the inhibitory effect of spexin on food intake, suggesting that GALR3, not GALR2, was involved in the anorectic effect of spexin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spexin was coevolved with the galanin/kisspeptin family, and it was confirmed that spexin could activate GALR2/3 receptors [ 4 ]. GALR2 antagonist M871 and GALR3 antagonist SNAP37889 had been used to the role of spexin in gastrointestinal motility [ 11 ], inflammatory pain [ 16 ], bile acid synthesis [ 8 ], lipolysis [ 24 ], and in vivo or in vitro studies. Our result demonstrated that SNAP37889 ( p < 0.05), not M871 ( p =0.430), significantly antagonized the inhibitory effect of spexin on food intake, suggesting that GALR3, not GALR2, was involved in the anorectic effect of spexin.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrated that spexin was involved in multiple biological and pathological roles [ 7 ]. It was reported that spexin had effects on regulating bile acid synthesis and metabolism [ 8 ], glucose metabolism, and ameliorated insulin resistance [ 9 , 10 ]. Spexin promoted rat stomach muscle contraction in the explant assay [ 1 ] and enhanced mouse gastrointestinal motility in vivo [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sassek et al [ 14 ] in their study observed that SPX may be strongly involved in the pathogenesis of diabetes or its recovery because of the effects of SPX on insulin secretion in vitro and in vivo and also on cell viability and proliferation. Lin et al [ 15 ] highlighted the role of SPX in bile acid synthesis and reported correlations between serum SPX and total cholesterol in rats.…”
Section: Discussionmentioning
confidence: 99%
“…BA metabolites were individually extracted and quantified from human samples (serum and stools) and rodents’ specimens (liver and ileal contents) as previously described. 3235 With mass spectrometry as the platform, a single 26-min acquisition method with positive/negative ion switching under the multiple reaction monitoring (MRM) mode was used for simultaneous quantification of 36 BA individuals and C4. The chemical usage and detail procedures are described in Supplementary methods .…”
Section: Methodsmentioning
confidence: 99%